Enviornmental Factors Effects on Asthma in the National population Health Survey - Gu, Rongfang (My University, 2003)
Asthma is one of the most common respiratory diseases in Canada. It not only brings pain to more than 7.8% of Canadians but it also costs millions of dollars every year. In this project we study the influence that environmental factors have on asthma based on the data from the National Population Health Survey (NPHS) conducted by Statistics Canada. A descriptive analysis is done first to get an initial understanding of the environmental factors' effects on asthma. Then we do a x2-test to test for the homogeneity of asthma distribution across the levels of each environmental factor. Most of the factors included in our study are significant except those representing whether living in the metropolitan areas of Montreal or Vancouver, the number of persons living in the household, and whether there are small children in the household. For ordinal variables we test for trend on asthma prevalence. The trend tests indicate that there are significant trends between asthma and most of the ordinal factors except for a few, including the number of bedrooms in the household and the number of cigarettes smoked daily by the daily smokers. Then odds ratio and relative risk analyses are done to obtain statistical insights on the relative risk of the factors. The result shows that living in Nova Scotia, Ontario and Quebec, urban areas, engaged in finance, community services, personal service, young, attend physical activities, born in Canada, white, single or widowed, separated, divorced, start smoking early, do not own the dwelling living in, female adult, male children, and overweight and underweight adult, are all contributing factors for asthma. To model and investigate the joint effect of factors on asthma prevalence, we use logistic and log-linear regression models. To avoid collinearity problems, a reduced number of predictors is used. The results suggest that environmental factors have a significant joint influence on asthma prevalence.
Keywords: enviornmental factor; asthma; national population health survey; national population